Domestic Tourist’s Motivation Consume Local Food: A Case Study in Bangka Belitung - Levyda, Levyda; Maulana, Lucky Hikmat (Jurnal Manajemen, 2024)
Consuming local food has the power to boost a destination’s economy and preserve its unique culture. At present, there is a disparity between the rise in the quantity of tourists visiting Bangka Belitung and the rise in their expenditure on consumption. The purpose of this study is to pinpoint the driving forces behind tourism spending. Purposive sampling was utilized in the study to gather data from visitors who had eaten local cuisine in Bangka Belitung. Samples were collected by means of the snowball method. Social media was used to distribute the questionnaires. There are 339 samples in all. Thirteen motivations were identified based on visitor experiences, as well as literature studies. These will be tested using factor analysis processed with SPSS. Two motivational groups were identified from the testing: social motivation and motivation to appreciate local cuisine. Authenticity of the food, tradition, culture, and social components are among the reasons people appreciate consuming local food. Emotions and social standing are components of social motivation. Part of the equation is sensory motivation. In order to effectively promote local food, sensory elements must be highlighted. The study concludes that managers in the travel business ought to understand more about the reasons behind tourists’ eating habits. It will therefore serve tourists more effectively, resulting in their satisfaction and loyalty to the local food, which will strengthen the local economy. It is suggested that interaction motivation be included in future studies.